Implementasi Data Mining pada Penjualan Kartu Perdana Internet di Purnama Ponsel Menggunakan Metode Algoritma Apriori - Sukri Adrianto; Nur Khasanah; Deasy Wahyuni (UIN Sunan Kalijaga Yogyakarta, 2020)
Purnama Ponsel is a mobile business which is engaged in selling internet starter packs. Internet starter packs are cards that are used with restrictions or limits on internet usage, where by using this internet starter pack the user can save credit because all activities use quotas except telephone (voice calls) and Short Message Service (SMS). Some companies compete by issuing internet premieres so as to reduce access costs. This competition can be seen from the number of internet starter packs that are sold simultaneously and know the inventory for the next month. So to facilitate the calculation of cell phone owners using data mining with apriori algorithm method to complete this research. Using the apriori algorithm method can help mobile full moon owners in the calculation process on full moon cellphones using the Tanagra application and is expected to reduce the number of cards that expire and can predict how many card supplies are needed for the following month.